What happens in the brain during recovery from exhaustive cycling in the heat? - De Pauw, K.; Roelands, B.; Vanparijs, J.; Marusic, U.; Tellez, H. F.; Knaepen, K.; Meeusen, R. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Accelerating the post-exercise recovery process beneficially influences subsequent exercise performance1. Although the effect of different recovery interventions on physiological parameters is well investigated, the question remains how recovery influences brain functioning. Therefore, the neurotrophin brain-derived neurotrophic factor (BDNF) and the relative EEG power spectrum were analyzed at baseline and during the post-exercise recovery period. Methods: After a maximal cycle test and familiarization trial, 9 trained male subjects (age: 22±3y; VO2max: 62±5mL/kg/min) performed 3 experimental trials in 30°C. Each trial consisted of two exercise tasks separated by 1h. The first was a 60min constant load trial, followed by a 30min time-trial (TT1). Thereafter, active recovery (AR; cycling at 80W), passive rest (PR) or cold water immersion (CWI; 15°C water) was applied for 15min. The second trial comprised a 12min time-trial (TT2). EEG was obtained at baseline, during recovery and before TT2. Blood samples were taken at baseline, before and after the recovery period. BDNF data (ELISA kit) were analyzed using ANOVA and paired t-tests. Power spectral data (discrete Fourier transform) were analyzed using Friedman and Wilcoxon tests. Results/Discussion: After CWI subjects maintained high power outputs during TT2, whereas after AR and PR subjects gradually declined the power output after the onset of TT22. Exhaustive cycling in the heat significantly reduced ß1power at prefrontal electrodes (P.0.038) indicating decreased state of activity in sensory and psychological information processing centers. Exercise as a physiological stressor increased ß2power at central electodes (P.0.028) and FC1, FC2 and Cz (P.0.086). AR and PR did not elicit any significant electrocortical alteration. CWI increased ß1power at Fz - F4 (P.0.038), and FP1 - FP2 (P.0.086). The rest period after CWI decreased ß2power at Cz (P=0.028), and FC1, FC2, C3 and C4 (P.0.086) back to pre-exercise levels. Exhaustive cycling significantly increased BDNF by 51.5% (P<0.001; baseline: 19.9±6.8ng/mL; post-exercise 26,9±10.4ng/mL). CWI significantly decreased BDNF compared to post-exercise (P=0.007; -39.9%), whereas AR showed a trend towards reduced BDNF (P=0.095; -25.2%) and PR showed no change (P=0.834; +3.2%). Conclusion: CWI beneficially influences the second cycling bout. CWI not only rapidly normalizes physiological parameters and serum BDNF levels, but also restores exercise-induced altered brain rhythms to rest levels.